2020
DOI: 10.3390/ani10071108
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Sarcocystis spp. in One-humped Camels (Camelus dromedarius) from Riyadh and Dammam, Saudi Arabia, via Histological and Phylogenetic Approaches

Abstract: Sarcocystis (S.) spp. are intracellular protozoan parasites that infect birds and animals, resulting in substantial commercial losses. Sarcocystis spp. have an indirect life cycle; canines and felines are known to act as final hosts, and numerous domestic and wild animals act as intermediate hosts. The presence of sarcocysts in camel meat may diminish its commercial quality. There is limited knowledge regarding the taxonomy and diagnosis of Sarcocystis spp. that infect camels in Saudi Arabia. In this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 35 publications
(45 reference statements)
2
7
0
Order By: Relevance
“…This study has helped to extend the findings of previous studies on choke in dromedary camels. It also complements other studies of oesophageal disorders in dromedary camels which have, separately, reported that lesions of sarcocystosis are commonly found in oesophageal tissues 31 …”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This study has helped to extend the findings of previous studies on choke in dromedary camels. It also complements other studies of oesophageal disorders in dromedary camels which have, separately, reported that lesions of sarcocystosis are commonly found in oesophageal tissues 31 …”
Section: Discussionsupporting
confidence: 83%
“…It also complements other studies of oesophageal disorders in dromedary camels which have, separately, reported that lesions of sarcocystosis are commonly found in oesophageal tissues. 31 …”
Section: Discussionmentioning
confidence: 99%
“…(S. aucheniae or S. masoni) from camels and suggests identification of Sarcocystis spp. with more taxa and different molecular markers, including 18S rRNA and cox 1 (15). Mohamed et al (26) also suggested using the hybrid approach to characterize the microbe, including Next-Generation Sequencing and conventional PCR combined with Sanger sequencing, and also using RFLP-PCR for characterization of Sarcocystis isolated from camel (27).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, PCR was performed to amplify a segment of the mitochondrial cytochrome c oxidase subunit 1 gene (cox 1) using the specific primer pairs of SF1 (ATGGCGTACAACAATCATAAAGAA) and SR9 (ATATCCATACCRCCATTGCCCAT). The amplified PCR product was approximately 1038 bp (14,15), and both negative and positive controls were included. The PCR products were sent to Shanghai Sangon Company (China) for bi-directional sequencing on an ABI PRISM TM 3730 XL DNA Analyzer using the BigDye Terminator v3.1 Cycle Sequencing Kit (Applied Biosystems, Foster City, CA, USA).…”
Section: Molecular Analysis Of Sarcocystismentioning
confidence: 99%
“…In this regard, the digestion method and histopathological analysis have been implemented for the analysis of microscopic sarcocysts in camels. Moreover, ultrastructural analysis, using transmission electron microscopy of the cyst wall appears very useful in the identification of sarcocysts [ 55 ]. Furthermore, several serological techniques, including enzyme-linked immunosorbent assay and an indirect fluorescent antibody test, were used for diagnosing infection.…”
Section: Discussionmentioning
confidence: 99%